2020
DOI: 10.1016/j.dsx.2020.08.038
|View full text |Cite
|
Sign up to set email alerts
|

Does the presence of diabetes mellitus confer an increased risk of stroke in patients with atrial fibrillation on direct oral anticoagulants? A systematic review and meta-analysis

Abstract: Does the presence of diabetes mellitus confer an increased risk of stroke in patients with atrial fibrillation on direct oral anticoagulants? A systematic review and meta-analysis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…An important cause of stroke is atrial fibrillation, and in a study of this relationship, persons with diabetes, although more likely to be anticoagulated with warfarin than nondiabetic persons with atrial fibrillation, had greater risk of stroke, although with improvement during the period from 1992 to 2019 24 . A meta‐analysis of studies of atrial fibrillation showed that those with diabetes had greater risk of stroke as well as of other vascular events and of mortality, with similar risk reduction comparing warfarin with direct oral anticoagulants 25 …”
Section: The Association Of Diabetes With Strokementioning
confidence: 97%
See 1 more Smart Citation
“…An important cause of stroke is atrial fibrillation, and in a study of this relationship, persons with diabetes, although more likely to be anticoagulated with warfarin than nondiabetic persons with atrial fibrillation, had greater risk of stroke, although with improvement during the period from 1992 to 2019 24 . A meta‐analysis of studies of atrial fibrillation showed that those with diabetes had greater risk of stroke as well as of other vascular events and of mortality, with similar risk reduction comparing warfarin with direct oral anticoagulants 25 …”
Section: The Association Of Diabetes With Strokementioning
confidence: 97%
“…24 A meta-analysis of studies of atrial fibrillation showed that those with diabetes had greater risk of stroke as well as of other vascular events and of mortality, with similar risk reduction comparing warfarin with direct oral anticoagulants. 25…”
Section: The Association Of Diabetes With Strokementioning
confidence: 99%
“…The healthcare burden of atrial fibrillation is increasing because of the accelerated aging of the population worldwide ( 2 ). Despite direct-acting oral anticoagulants effectively reducing stroke risk ( 3 ), atrial fibrillation was still associated with a 1.95-fold increased risk of all-cause mortality ( 4 ). Therefore, risk stratification of survival outcomes in atrial fibrillation patients is an urgent demand for better clinical management.…”
Section: Introductionmentioning
confidence: 99%
“…DM is considered to be a burden in the clinical course of AF. There is a well-established link between DM or poorly regulated blood glucose levels and increased mortality in patients with AF [ 6 , 21 , 24 , 63 , 77 ]. In particular, a positive linear correlation exists between HbA1c and mortality rates.…”
Section: Relevance Of Glycated Hemoglobin Measurement In Afmentioning
confidence: 99%
“…Although the epidemiology and implications of the AF and DM comorbidity seem to be well described in the current literature [ 6 , 7 ], the precise underlying pathogenic mechanisms still remain an issue of debate [ 8 ]. Significant questions also remain regarding the effect of glycemic control on the development and clinical course of AF.…”
Section: Introductionmentioning
confidence: 99%